Western historiography in Asia circulation, critique and comparison - Wang, Q. Edward 1958-; Okamoto, Michihiro; Longguo, Li (De Gruyter Oldenbourg, 2022)
This volume provides a unique and critical perspective on how Chinese, Japanese and Korean scholars engage and critique the West in their historical thinking. It showcases the dialogue between Asian experts and their Euro-American counterparts and offers valuable insights on how to challenge and overcome Eurocentrism in historical writing
Keywords: Geschichte 470 v. Chr.-2022; Geschichte 1950-2022; Asiatische Geschichte; Euroamerikanische Geschichtsschreibung; Eurozentrismus; Historiographie; Geschichtstheorie; Geschichtsschreibung; China; Japan; Westliche Welt; Korea; Aufsatzsammlung